PENGENALAN PERAN TEKNIK KIMIA DALAM APLIKASI KEAMANAN PANGAN (FOOD SAFETY) DI DUSUN PELEM WULUNG BANGUNTAPAN KABUPATEN BANTUL - Gusmarwani, Sri Rahayu (JURNAL GAUNG INFORMATIKA, 2016)
Three pilars of an university activities are Education and Teaching, Research, and  Community Service. Community was as one of universityâs stake holder need some  knowledge and technologies that could be applied for their lives. Community service  was done in order for applicating and publicating of science and technology.  Community service was also done for minimizing gap between university and  community. Chemical Engineering, one of Department in Institute Technology and Science  AKPRIND Yogyakarta, take a role play in food safety management, cause one of curriculum in Chemical Engineering was Food Technology. Food Safety in chemical  engineering mean activities or systems that can be reduce, eliminate or protect food  from food hazardous materials.